High performance concrete deicer and cold resistant high performance concrete for cold regions

By adding specially designed antifreeze agents to high-performance concrete and utilizing raw materials such as composite phase change materials and nanoparticles, the problems of insufficient concrete strength and freeze-thaw loss in frigid regions have been solved, achieving high durability and good mechanical properties.

CN116750987BActive Publication Date: 2025-12-23ALAR ZHEJIAN NEW BUILDING MATERIALS GRP CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310648524.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-02
Publication Date
2025-12-23
Estimated Expiration
2043-06-02

AI Technical Summary

Technical Problem

In frigid regions, conventional high-performance concrete cannot achieve the expected high durability and mechanical properties under low-temperature conditions, and is prone to significant strength loss due to frequent freeze-thaw cycles.

Method used

The specially designed high-performance concrete antifreeze agent contains raw materials such as sodium thiocyanate, calcium nitrate, composite phase change material and carbide slag nanopowder. By controlling the ratio of phase change material to silica hollow microspheres and the mixing process, the hydration reaction is promoted, temperature fluctuations are buffered, frost heave stress is reduced, and interfacial bonding performance is enhanced.

Benefits of technology

It significantly improves the compressive strength and mechanical properties of concrete after freeze-thaw cycles, with the highest compressive strength reaching 58.2 MPa and the strength loss after freeze-thaw cycles being only 1.2-1.4%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application discloses a high-performance concrete special antifreeze for severe cold regions and cold-resistant high-performance concrete, and the raw materials of the antifreeze include 6-10 parts of sodium thiocyanate, 5-8 parts of calcium nitrate, 7-10 parts of a composite phase change material, 3-5 parts of nano calcium carbide slag powder and 3 parts of sodium citrate in terms of mass fraction. The raw materials of the high-performance concrete include 330-360 parts of ordinary Portland cement, 60-90 parts of fly ash, 630-660 parts of fine aggregate, 1150-1200 parts of coarse aggregate and 8-10 parts of high-performance polycarboxylic acid water reducing agent in terms of mass fraction; and the high-performance concrete special antifreeze for severe cold regions is further included and the dosage is 7.5-9 parts. The antifreeze provided by the application is specially applied to severe cold regions (temperature fluctuation reaches-15 DEG C to-5 DEG C, and even reaches-20 DEG C in extreme regions), and in addition to antifreezing and early strength promotion, the working performance of concrete is ensured, the compressive strength of the concrete added with the antifreeze reaches 58.2 MPa, and the compressive strength loss after 200 freeze-thaw cycles is only 1.2-1.4%.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of concrete antifreeze, in particular to a special antifreeze for high-performance concrete used in severe cold regions and cold-resistant high-performance concrete. BACKGROUND

[0002] In the three-north region and the Qinghai-Tibet Plateau region of China, the duration of winter is long, and the air temperature is mostly between-15℃ and-5℃. In some areas, the extreme minimum temperature can even reach-40℃. With the development of engineering construction, the long cold temperature has brought many problems to concrete winter construction. Over the years, under the joint efforts of domestic and foreign experts and construction technical personnel, China's winter construction technology has made great progress. At present, in order to improve the frost resistance of concrete used in low temperature / negative temperature environment, the method of adding antifreeze is mainly used. The antifreeze realizes antifreeze mainly by reducing the freezing point, eliminating the internal frost heaving stress (expansion stress), improving the early strength performance, and improving the work performance.

[0003] The average temperature in the plateau and cold region of China is very low, the freeze-thaw cycle is frequent, and the air is dry. If the conventional high-performance concrete is directly used as the building material in the plateau and cold region, it may not achieve the expected high durability and mechanical properties, and even significant strength loss may occur. Therefore, how to use appropriate antifreeze and high-performance concrete to meet the needs of construction in these cold regions is a difficult problem facing building engineering experts and technical personnel at present. SUMMARY

[0004] In view of the deficiencies of the prior art, the present application provides a special antifreeze for high-performance concrete used in severe cold regions and cold-resistant high-performance concrete, which is realized by the following technology.

[0005] The special antifreeze for high-performance concrete used in severe cold regions comprises, by mass fraction, sodium thiocyanate 6-10 parts, calcium nitrate 5-8 parts, composite phase change material 7-10 parts, calcium carbide slag nano powder 3-5 parts, and sodium citrate 3 parts.

[0006] The preparation method of the composite phase change material is as follows: liquid phase change material with a phase change temperature of 0-10℃ is taken, silica hollow microspheres are added, vacuum stirring is performed for 30-60min, and then normal pressure stirring is performed for 10-20min in an environment lower than the phase change temperature to obtain the composite phase change material; and the mass ratio of the phase change material to the silica hollow microspheres is (0.3-0.5):1.

[0007] Preferably, in the preparation method of the composite phase change material, the mass ratio of the phase change material to the silica hollow microspheres is 0.45:1.

[0008] Preferably, the phase change material is n-tetradecane and / or n-pentadecane.

[0009] More preferably, the raw materials include sodium thiocyanate 9 parts, calcium nitrate 7 parts, composite phase change material 9 parts, calcium carbide slag nano powder 4 parts, and sodium citrate 3 parts.

[0010] The application also provides a preparation method of the special antifreezing agent for high-performance concrete, which comprises the following steps: directly stirring and uniformly mixing sodium thiocyanate, calcium nitrate, composite phase change material, calcium carbide slag nano powder and sodium citrate in an environment below the phase change temperature.

[0011] The application also provides a cold-resistant high-performance concrete, which comprises the following raw materials in parts by mass: ordinary Portland cement 330-360 parts, fly ash 60-90 parts, fine aggregate 630-660 parts, coarse aggregate 1150-1200 parts and high-performance polycarboxylate superplasticizer 8-10 parts; and the special antifreezing agent for high-performance concrete for severe cold regions provided by the application is also included and the amount is 7.5-9 parts.

[0012] Preferably, the raw materials of the cold-resistant high-performance concrete comprise the following components in parts by mass: ordinary Portland cement 350 parts, fly ash 70 parts, fine aggregate 650 parts, coarse aggregate 1180 parts and high-performance polycarboxylate superplasticizer 9 parts; and the special antifreezing agent for high-performance concrete provided by the application is also included and the amount is 8 parts.

[0013] The high-performance concrete needs to use fly ash beads and other materials in addition to the raw materials in order to achieve super-high mechanical strength and ensure good working performance and self-compacting performance; the commonly used Portland cement has a mark of P·O42.5, and other raw materials can be directly purchased on the market. When the conventional high-performance concrete is used in severe cold regions, the hydration heat reaction between the raw materials is seriously affected due to the very low ambient temperature, which leads to a significant lack of early strength, and the requirement for maintenance is also higher, that is, the standard maintenance is required first, and then the constant low-temperature maintenance is required.

[0014] The special antifreezing agent provided by the application is specially designed for the high-performance concrete used in severe cold regions, and the sodium thiocyanate, calcium nitrate and calcium carbide slag nano powder in the raw materials can significantly improve the problem of slow hydration reaction caused by the increase of the solubility of Ca(OH)2 in the low-temperature environment; the crystal nucleus effect of the calcium carbide slag nano powder can also induce the attachment and generation of calcium hydroxide crystals, and finally through the synergistic effect of multiple parties, the hydration reaction is finally promoted to proceed quickly.

[0015] The composite phase change material is prepared by controlling the dosage ratio of the phase change material and the hollow silica microspheres and a special vacuum stirring preparation process, so that part of the phase change material is embedded in the hollow silica microspheres, and the other part is attached to the surface of the hollow silica microspheres, so that the inside of the hollow silica microspheres is in a semi-filled state to different degrees. The hollow structure of the hollow silica microspheres has good heat preservation effect and can reduce the influence of the low / negative temperature environment on the inside of the concrete. The steel fiber used in the high-performance concrete has certain heat conduction performance. Therefore, through the balance of the effects of the two, the temperature distribution inside the high-performance concrete is basically consistent, and the hydration reaction temperature environment inside the concrete is effectively improved. In the composite phase change material, the hollow silica microspheres themselves have the property of volcanic ash, which can enhance the interface cementing performance and avoid the migration of water, chloride ions and sulfate ions, thereby ensuring the durability of the concrete to a certain extent. Because the environmental temperature fluctuates greatly in the low / negative temperature environment, the fluctuation range often reaches-15℃-5℃, and the freeze-thaw frequency is very high. If it is not controlled, it will inevitably lead to cracking inside the concrete due to the frost heaving stress. The phase change material inside and outside the hollow silica microspheres can buffer and neutralize the frost heaving stress during the hydration reaction process and the normal use process of the concrete, thereby minimizing the loss of the mechanical properties of the concrete caused by temperature fluctuations.

[0016] Compared with the prior art, the freeze-proof agent provided by the application is specially applied in severe cold regions (temperature fluctuation reaches-15℃-5℃, and even-20℃ in extreme regions) and is specially developed for high-performance concrete. In addition to being able to play a very good role in preventing freezing and promoting early strength and ensuring the working performance of the concrete, the freeze-proof agent can also effectively avoid the loss of mechanical properties of the high-performance concrete caused by repeated freezing and thawing during long-term application. The high-performance concrete prepared by adding the freeze-proof agent of the application has a compressive strength of up to 58.2MPa, and the loss of the compressive strength of the concrete after 200 freeze-thaw cycles is only 1.2-1.4%. DETAILED DESCRIPTION

[0017] The technical solutions of the application will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the application, rather than all the embodiments. Based on the embodiments in the application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the application.

[0018] The calcium carbide slag nano-powder used in the following examples and comparative examples is prepared by grinding, with a grading of 0.20-0.32 μm; the phase change material used is n-tetradecane, with a phase change temperature of 5.8℃; the silica hollow microspheres are 200-250 mesh; and the other raw materials are all commercially available.

[0019] The composite phase change material used in the following examples and comparative examples is prepared by the following method, unless otherwise specified: liquid n-tetradecane is taken, and silica hollow microspheres are added thereto, followed by stirring at 100 rpm under a vacuum of 2000 Pa for 45 min, and then stirring at 100 rpm under normal pressure (0.1 MPa) at 0℃ for 20 min, to obtain the composite phase change material; the mass ratio of the phase change material to the silica hollow microspheres is 0.45:1.

[0020] Example 1

[0021] The antifreezing agent provided in this example comprises, by mass fraction, sodium thiocyanate 9 parts, calcium nitrate 7 parts, composite phase change material 9 parts, calcium carbide slag nano-powder 4 parts, and sodium citrate 3 parts.

[0022] Example 2

[0023] The antifreezing agent provided in this example comprises, by mass fraction, sodium thiocyanate 6 parts, calcium nitrate 8 parts, composite phase change material 7 parts, calcium carbide slag nano-powder 5 parts, and sodium citrate 3 parts.

[0024] Example 3

[0025] The antifreezing agent provided in this example comprises, by mass fraction, sodium thiocyanate 10 parts, calcium nitrate 5 parts, composite phase change material 10 parts, calcium carbide slag nano-powder 3 parts, and sodium citrate 3 parts.

[0026] Example 4

[0027] The antifreezing agent provided in this example comprises the same raw materials as in Example 1, except that the mass ratio of n-tetradecane to silica hollow microspheres used in the preparation of the composite phase change material is 0.3:1.

[0028] Comparative Example 1

[0029] The antifreezing agent provided in this comparative example comprises, by mass fraction, sodium thiocyanate 9 parts, calcium nitrate 7 parts, calcium carbide slag nano-powder 4 parts, and sodium citrate 3 parts; no phase change material is added.

[0030] Comparative Example 2

[0031] The antifreeze provided by the present comparative example, the raw materials include sodium thiocyanate 9 parts, calcium nitrate 7 parts, phase change material 9 parts, calcium carbide slag nano powder 4 parts, sodium citrate 3 parts by mass fraction; the phase change material used is ordinary n-tetradecane, and the n-tetradecane is not treated with silica hollow microsphere or any other hollow microsphere material.

[0032] Test example: performance test of high-performance concrete

[0033] The antifreeze prepared by the above examples and comparative examples is used to prepare high-performance concrete, and the formula of the high-performance concrete is shown in Table 1.

[0034] Table 1 Formula of high-performance concrete

[0035]

[0036] The concrete slurry prepared by the above examples and comparative examples is molded and hardened by a conventional method to form a 100mm×100mm×100mm compressive strength test piece; according to the antifreeze product test method of JC475 “Concrete Antifreeze”, the test piece is first subjected to-15℃ negative temperature curing for 7d, and then standard curing for 28d, and the mechanical property test is carried out according to the “Standard for Mechanical Property Test of Ordinary Concrete” (GB / T50081-2019). The high-performance concrete without adding any antifreeze is molded in a normal temperature environment and subjected to conventional standard curing, which serves as a blank group; the high-performance concrete without adding any antifreeze is molded in a normal temperature environment, first subjected to-15℃ negative temperature curing for 7d, and then standard curing for 28d, which serves as a blank group two. Taking the test data of the control group one as the benchmark, the compressive strength ratio of each example and comparative example is calculated.

[0037] The mechanical strength loss of each test piece after 200 freeze-thaw cycles is tested, and the specific method is as follows: after the curing of the concrete test piece is completed, it is soaked in normal temperature water for 4d, and the water level is about 20mm higher than the upper surface of the test piece; after soaking, the test piece is taken out and the surface water is wiped off, and the test piece is placed in a-15℃ constant temperature environment for freezing for 4h; after freezing, it is placed in normal temperature water for thawing, and the thawing time is 4h, and the water level is about 20mm higher than the upper surface of the test piece; after thawing, one freeze-thaw cycle is completed. The test piece is taken out and put into a freezer for the next cycle test, a total of 200 cycles. The test results are shown in Table 2.

[0038] Table 2 Test results of concrete performance

[0039]

[0040] From the test results of the above table, it can be seen that, compared with a group of high-performance concrete without using antifreeze and with standard curing, although no antifreeze is used, there is no effect on the mechanical properties due to the use of conventional standard curing; however, due to the lack of antifreeze effect, the compressive strength loss after freeze-thaw cycle is more obvious. When compared with a group of high-performance concrete without using antifreeze and with standard curing after negative temperature curing, due to the lack of antifreeze effect, the mechanical properties are the worst, and the compressive strength loss after freeze-thaw cycle is also very large.

[0041] Through comparison of Examples 1-3, it can be found that the amount of each raw material of the antifreeze has a certain influence on the performance of the high-performance concrete after adding the antifreeze, but the difference between them is not large, for example, the compressive strength can reach more than 56 MPa, and the compressive strength loss after freeze-thaw cycle is low.

[0042] Through comparison of Example 1, Comparative Examples 1 and 2, Blank Group 1 and Blank Group 2, it can be seen that when the antifreeze of Comparative Example 1 does not add phase change material, there will be obvious compressive strength loss after freeze-thaw cycle, but due to the effect of the antifreeze, the loss is relatively small. The method of first negative temperature curing and then standard curing has a significant adverse effect on the mechanical strength. When the antifreeze of Comparative Example 2 does not add silica hollow microspheres, there will be obvious compressive strength loss after freeze-thaw cycle, and the mechanical strength will also decrease significantly; but due to the effect of the phase change material, the degree of compressive strength loss and the degree of decrease of mechanical properties are slightly eased compared with Comparative Example 1.

[0043] The above specific embodiments describe the implementation of the present application in detail, but the present application is not limited to the specific details in the above embodiments. Within the scope of the claims and technical concepts of the present application, the technical solutions of the present application can be modified and changed in many simple ways, and these simple modifications all belong to the protection scope of the present application.

Claims

1. A high performance concrete deicer for use in cold climates, characterized in that, The raw materials include sodium thiocyanate 6-10 parts, calcium nitrate 5-8 parts, composite phase change material 7-10 parts, calcium carbide slag nano powder 3-5 parts, and sodium citrate 3 parts by mass fraction. The preparation method of the composite phase change material is: taking liquid phase change material with a phase change temperature of 0-10 DEG C, adding hollow silica microspheres into the liquid phase change material, vacuum stirring for 30-60 min, and then normal pressure stirring for 10-20 min in an environment lower than the phase change temperature to obtain the composite phase change material; the mass ratio of the phase change material to the hollow silica microspheres is (0.3-0.5):

1.

2. The high performance concrete deicer for cold regions according to claim 1, characterized by, In the preparation method of the composite phase change material, the mass ratio of the phase change material to the hollow silica microspheres is 0.45:

1.

3. The high performance concrete deicer for cold regions according to claim 1, characterized by, The phase change material is n-tetradecane and / or n-pentadecane.

4. The high performance concrete deicer for cold regions according to any one of claims 1 to 3, characterized by, The raw materials include sodium thiocyanate 9 parts, calcium nitrate 7 parts, composite phase change material 9 parts, calcium carbide slag nano powder 4 parts, and sodium citrate 3 parts by mass fraction.

5. A method for preparing the high performance concrete deicer for cold regions according to claim 1, characterized in that, The preparation method is: stirring and mixing sodium thiocyanate, calcium nitrate, composite phase change material, calcium carbide slag nano powder, and sodium citrate directly and uniformly under an environment lower than the phase change temperature.

6. A cold-resistant high-performance concrete, characterized by, The raw materials include ordinary portland cement 330-360 parts, fly ash 60-90 parts, fine aggregate 630-660 parts, coarse aggregate 1150-1200 parts, and high-performance polycarboxylic acid water reducer 8-10 parts by mass fraction; and the high-performance concrete antifreeze agent for severe cold regions in any one of claims 1-3 is further included and the amount is 7.5-9 parts.

7. The cold-resistant high-performance concrete according to claim 6, characterized in that, The raw materials include ordinary portland cement 350 parts, fly ash 70 parts, fine aggregate 650 parts, coarse aggregate 1180 parts, and high-performance polycarboxylic acid water reducer 9 parts by mass fraction. The high-performance concrete antifreeze agent for severe cold regions in any one of claims 1-3 is further included and the amount is 8 parts.

Citation Information

Patent Citations

  • Concrete deicing chemical containing thiocyanate

    CN101508534A

  • Impervious marine concrete anti-corrosive admixture and preparation method thereof

    CN109455977A

  • Expanded graphite adsorption tetradecane low-temperature phase change cement concrete and preparation method thereof

    CN111499312A

  • Composite alkali-activated lithium slag low-temperature early-strength concrete and preparation method thereof

    CN114349431A